Prohibitin 2 represents a novel nuclear AKT substrate during all‐trans retinoic acid–induced differentiation of acute promyelocytic leukemia cells. Issue 5 (12th February 2014) - Bavelloni, Alberto; Piazzi, Manuela; Faenza, Irene; Raffini, Mirco; D'Angelo, Antonietta; Cattini, Luca; Cocco, Lucio; Blalock, William L.
ABSTRACT: The AKT/PKB kinase is essential for cell survival, proliferation, and differentiation; however, aberrant AKT activation leads to the aggressiveness and drug resistance of many human neoplasias. In the human acute promyelocytic leukemia cell line NB4, nuclear AKT activity increases during all‐ trans retinoic acid (ATRA)‐mediated differentiation. As nuclear AKT activity is associated with differentiation, we sought to identify the nuclear substrates of AKT that were phosphorylated after ATRA treatment. A proteomics‐based search for nuclear substrates of AKT in ATRA‐treated NB4 cells was undertaken by using 2D‐electrophoresis/mass spectrometry (MS) in combination with an anti‐AKT phospho‐substrate antibody. Western blot analysis, an in vitro kinase assay, and/or site‐directed mutagenesis were performed to further characterize the MS findings. MS analysis revealed prohibitin (PHB)‐2, a multifunctional protein involved in cell cycle progression and the suppression of oxidative stress, to be a putative nuclear substrate of AKT. Follow‐up studies confirmed that AKT phosphorylates PHB2 on Ser‐91 and that forced expression of the PHB2(S91A) mutant results in a rapid loss of viability and apoptotic cell death. Activation of nuclear AKT during ATRA‐mediated differentiation results in the phosphorylation of several proteins, including PHB2, which may serve to coordinate nuclear–mitochondrial events during differentiation.—Bavelloni, A., Piazzi, M., Faenza, I., Raffini, M., D'Angelo, A., Cattini, L., Cocco, L., Blalock, W. L. Prohibitin 2 represents a novel nuclear AKT substrate during all‐ trans ‐retinoic acid‐induced differentiation of acute promyelocytic leukemia cells. FASEB J . 28, 2009–2019 (2014). www.fasebj.org